Implementasi Kalimat Efektif terhadap Penggunaan Bahasa Gaul - Nurchalistiani Budiana; Didik Tri Setiyoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to find out the slang used by Muhadi Setiabudi Brebes University students in WhatsApp to lecturers of the Indonesian Language and Literature Education study program. This research uses descriptive qualitative research. The data collection technique used structured interviews. The author did this with several students who at that time communicated using effective sentences either outside the campus or during teaching and learning activities. Types of data and data sources obtained directly from the field through interviews with students who carry out activities with social media. The results of the research on the slang used by UMUS students in WhatsApp to lecturers of the Indonesian language and literature education study program: sociolinguistic reviews include: 1) colloqial slang, 2) variations in terms of speakers, 3) diction, 4) meaning in sentences, 5) emphasis Specific targets that will be achieved, namely students are expected to be able to use the effectiveness of sentences against usage on social media. So that the existence of effective sentences can be applied in social life. Keywords: Effective Sentences, Slang